Imaging Neurochemistry and Brain Structure Tracks Clinical Decline and Mechanisms of ALS in Patients - Andronesi, Ovidiu C.; Nicholson, Katharine; Jafari-Khouzani, Kourosh; Bogner, Wolfgang; Wang, Jing; Chan, James; Macklin, Eric A.; Levine-Weinberg, Mark; Breen, Christopher; Schwarzschild, Michael A.; Cudkowicz, Merit; Rosen, Bruce R.; et al. (Frontiers in Neurology, 2020)
Background. Oxidative stress and protein aggregation are key mechanisms in ALS disease. Reduced glutathione (GSH) is the most important intra-cellular antioxidant that protects neurons from reactive oxygen species. We hypothesized that levels of GSH measured by MR spectroscopic imaging (MRSI) in the motor cortex and corticospinal tract are linked to clinical trajectory of ALS patients. Objectives. Investigate the value of GSH imaging to probe clinical decline of ALS patients in combination with other neurochemical and structural parameters. Methods. Twenty-four ALS patients were imaged at 3T with an advanced MR protocol. Mapping GSH levels in the brain is challenging and for this purpose we used an optimized spectral-edited 3D MRSI sequence with real-time motion and field correction to image glutathione and other brain metabolites. In addition, our imaging protocol included: i) an adiabatic T1 sequence to image macromolecular fraction of brain parenchyma, ii) DTI for white matter tractography, and iii) high-resolution anatomical imaging. Results. We found GSH in motor cortex (r = -0.431, p = 0.04) and corticospinal tract (r = -0.497, p = 0.016) inversely correlated with time between diagnosis and imaging. N-acetyl-aspartate in motor cortex inversely correlated (r = -0.416, p = 0.049), while mean water diffusivity (r = 0.437, p = 0.033) and T1 (r = 0.482, p = 0.019) positively correlated with disease progression measured by imputed change in revised ALS Functional Rating Scale. Conclusions. Our study suggests that a panel of biochemical and structural imaging biomarkers defines a brain endophenotype, which can be used to time biological events and clinical progression in ALS patients. Such a quantitative brain endophenotype may stratify ALS patients into more homogeneous groups for therapeutic interventions, compared to clinical criteria.